Microgripper Using Soft Microactuators for Manipulation of Living Cells - Shunnosuke Kodera; Tomoki Watanabe; Yoshiyuki Yokoyama; Takeshi Hayakawa (Micromachines, 2022)
We present a microgripper actuated by a soft microactuator for manipulating a single living cell. Soft actuators have attracted attention in recent years because their compliance which can adapt to soft targets. In this study, we propose a microgripper actuated by soft thermoresponsive hydrogels. The thermoresponsive gel swells in water when the temperature is low and shrinks when the temperature is high. Therefore, the microgripper can be driven by controlling the temperature of the thermoresponsive gel. The gels are actuated by irradiating with infrared (IR) laser to localize heating. The actuation characteristics of the gripper were theoretically analyzed and we designed a gripper that gripped a ≈10 µm size cell. Additionally, we succeeded in actuating the fabricated microgripper with laser irradiation and gripping a single living cell.